Asynchronous Replication Timing: A Mechanism for Monoallelic Choice During Development - Bergman, Yehudit; Simon, Itamar; Cedar, Howard (Frontiers in Cell and Developmental Biology, 2021)
Developmental programming is carried out by a sequence of molecular choices that epigenetically mark the genome to generate the stable cell types which make up the total organism. A number of important processes, such as genomic imprinting, selection of immune or olfactory receptors and X-chromosome inactivation in females are dependent on the ability to stably choose one single allele in each cell. In this perspective, we propose that asynchronous replication timing serves as the basis for a sophisticated universal mechanism for mediating and maintaining these decisions.